A narrativa a caminho do narrar, ou do que fal(h)a em Lobo Antunes - Santos, Maicon Araújo dos (2018)
This work speaks of the narrative. Focuses on this speech, on the what it can say and on the ways in which it operates this diction. This research is absent from the place it deserves to go out looking for another, another place where there is no place, but only a possibility, where we settled in less as researchers than listeners speech mysterious to narrate. We circulate in this. Taken by the regime of signs of fragments of sentences and the words of the António Lobo Antunes’ speech (1942), we entered the bersgoniana duration of the flow of time that continues, not ending the event, which becomes infinite, open to the potential of the happening, dying infinitely without dying. It is the place of origin benjaminiana, pure vortex of a ceaseless becoming, which encompasses everything in a whirlwind that confuses memories, places, subjects, language. It is the voice of disorganized subject, disorganism-subject, who can only speak in the voice of the narrative’s unrepresentative without own language. It is the memory that can not represent the past, fails, change it in a speech desiring, stammering, impossible to mean. This listening, reading this (which is the research) appropriates of a thinking speech became of the voices of Friedrich Nietzsche, Martin Heidegger, Deleuze, Baruch Spinoza, Maurice Blanchot, Michel Foucault, Jacques Derrida, Walter Benjamin, Georges Bataille, Giorgio Agamben. Easily identifies this polyphony, among other considerations, the central issues on which these authors have addressed: language, memory and subject (or experience). The ideas offered by these thinkers reverberated in other propositions on writing, the writer, the dimensions and the art politics, also present in the voices of other theorists, artists, writers who take part here as well. It is a work about the (im)possibility of meaning of this speech in which creep Simone, Celina, Mimi, Fatima Cristina, her father, Alice, subjectivity in becoming the deed that is established in Exortação aos crocodilos (1999), in Comissão das Lágrimas (2013), and Caminho como uma casa em chamas (2014). There is a babble that makes the language vibrate in these novels; a almost-speech that happens to promote the inconsistency of the subjects of the narrative as organisms, and of the language as a structure, both happenning as the movement of the opening of the being of the language, where it arises and speaks the thing itself, the being of the language happening in speech without voice to say infinitely. This is almost to say that he speaks in the narrative he wishes to narrate; it is the one we are seeking to hear.